Evaluation of critical factors for typhoon-triggered landslide and subsequent debris flow in the Philippines using physically based models - Christian Gaviola John; Chieh Chao Kuo; Bencure Jannet (E3S Web of Conferences)
This study employs physically based modeling techniques to evaluate factors that triggered the catastrophic landslide that occurred in Kantagnos Village, Baybay City, Leyte, Philippines, during Typhoon Megi in 2022. The TRIGRS and DEBRIS-2D models simulated transient infiltration effects from four days of continuous rainfall, assessing pore water pressure changes and delineating hazard zones. Parametric analyses on critical parameters—such as fstrength characteristics, soil thickness, and water table conditions—were conducted to predict spatiotemporal changes in the factor of safety. The results of the analyses indicated that the accuracy of the model could reach up to 79.23%, as evaluated by receiver operating characteristic analysis, with area zoning based on bedding plane orientation improving this by 8.23%. DEBRIS-2D effectively simulated debris flow motion and deposition areas validated against field observations. The combined use of TRIGRS and DEBRIS-2D delineated hazard zones, with 93.97% of the area within the actual debris flow boundary predicted. Key parameters, including slope geometry, material yield stress, and the quality of the digital terrain model, are crucial for predicting debris flow distance and velocity. These findings offer a valuable benchmark for developing a framework for slope disaster analysis and risk management in the region.